2021
DOI: 10.1038/s41467-021-26131-z
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-related synaptic pathology causes autism spectrum disorder-associated functional hyperconnectivity

Abstract: Postmortem studies have revealed increased density of excitatory synapses in the brains of individuals with autism spectrum disorder (ASD), with a putative link to aberrant mTOR-dependent synaptic pruning. ASD is also characterized by atypical macroscale functional connectivity as measured with resting-state fMRI (rsfMRI). These observations raise the question of whether excess of synapses causes aberrant functional connectivity in ASD. Using rsfMRI, electrophysiology and in silico modelling in Tsc2 haploinsuf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 117 publications
7
82
0
Order By: Relevance
“…Moreover, in humans, the aberrant connections in the DMN or/and in its interplay with other networks have been found to constitute the "connectopathy" in many neurologic conditions such as Attention-deficit/hyperactivity disorder (ADHD) (Uddin et al, 2008), Autism spectrum disorder (ASD) (Uddin et al, 2019), Alzheimer's disease and aging (Toga and Thompson, 2014). Notably, a similar "connectopathy" involving aberrant rodent's DMN was also discovered in recent studies using transgenic mice for Autism Spectrum Disorder (Pagani et al, 2021) and Alzheimer's disease (Adhikari et al, 2021). Despite these similarities across rodents and humans, discrepancies remain.…”
Section: Homologous Functional Network Across Speciesmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, in humans, the aberrant connections in the DMN or/and in its interplay with other networks have been found to constitute the "connectopathy" in many neurologic conditions such as Attention-deficit/hyperactivity disorder (ADHD) (Uddin et al, 2008), Autism spectrum disorder (ASD) (Uddin et al, 2019), Alzheimer's disease and aging (Toga and Thompson, 2014). Notably, a similar "connectopathy" involving aberrant rodent's DMN was also discovered in recent studies using transgenic mice for Autism Spectrum Disorder (Pagani et al, 2021) and Alzheimer's disease (Adhikari et al, 2021). Despite these similarities across rodents and humans, discrepancies remain.…”
Section: Homologous Functional Network Across Speciesmentioning
confidence: 89%
“…A great example of this is seen in studies of Autism Spectral Disorder (ASD) where genetic alterations play a large role in the development of the disease ( Sandin et al, 2017 ). In such efforts, the use of ASD rodent models containing gene-specific mutations has proven incredibly useful in the study of underlying dysfunctions in brain connectomes and functional connectivity ( Pagani et al, 2021 ; Zerbi et al, 2021 ). However, choosing a rodent model must be done carefully as many variables, such as the difference in brain structure and function between rodents and humans as well as the type of rodent used ( Jonckers et al, 2011 ; Ellenbroek and Youn, 2016 ), act as contributing factors to the efficacy of the model.…”
Section: Applicationsmentioning
confidence: 99%
“…This notion is epitomized by the observation of intact rsfMRI coupling among brain regions not directly structurally connected as in the case of acallosal humans, primates, and rodents 7 , 14 , 15 . Moreover, rsfMRI network topography can dynamically reconfigure in response to local perturbations 16 or pathological processes 17 . In keeping with this, neurological disorders such as Parkinson’s disease, stroke, and Alzheimer’s disease have been often found to be associated with unexpectedly increased interareal rsfMRI connectivity despite the loss of cortical function characterizing these conditions 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In the preclinical setting, mouse models are utilized with the intention of better under-standing human neuropathology. For instance, in the context of autism spectrum disorders, a plethora of studies using mouse models have reported on the neurobiological and neuroanatomical phenotypes that arise from mutations at specific genetic loci (3133) . It is common for researchers involved in translational neuroscience to rely on findings of this kind to make inferences about the human disorder.…”
Section: Discussionmentioning
confidence: 99%